Scratch Assisted Physics Learning with a STEM Approach in the Pandemic Era to Develop 21st Century Learning Skills - Yulianti, D.; Sugianto, S.; Ngafidin, K. M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This century demands that everyone has 21st-century skills. The Covid-19 pandemic era has an impact on education, however, to face the global era, 21st-century skills must still develop in higher education including 21st-century learning skills called 4C skills (Creative, Critical, Collaboration, Communication). The survey of results on students participating in the Mechanics I course shows that creative and critical thinking skills are in a low category, collaboration and communication skills are also in the low category. This study aims to develop 4C skills in the pandemic era through learning Physics in Mechanics course with a Science Technology Engineering and Mathematics (STEM) approach, assisted by Scratch, and to know students’ responses to the applied learning. The research subjects were students in the third semester, who took the Mechanics I course as many as 110 people and were divided into three groups. The research method is a quasi-experiment one-group pretest-posttest design. The research instrument consists of essay tests to measure creative and critical thinking skills and observation sheets to measure collaboration and communication skills. The results of data analysis demonstrated that students' 4C skills increased, the average is in the medium category.